The Motherhood Penalty of Immigrants in France: Comparing the Motherhood Wage Penalty of Immigrants From Europe, the Maghreb, and Sub-Sahara With Native-Born French Women - Achouche, Noa (Frontiers in Sociology, 2022)
To date, relatively few studies analyzed the motherhood penalty as experienced by immigrant women. The principal objective of this research is to establish whether the negative effect of motherhood on wages is higher for immigrants than it is for the native population; and how this effect may vary across different immigrant regions of origin. Using data from the Enquête Revenus Fiscaux et Sociaux from 2009 to 2012 (INSEE, 2009-2012), a series of linear regression models were calculated to examine whether the effect of motherhood on wages differs for immigrant women and native women; and to what extent this effect varies across different immigrant origin groups. Specifically, this study explores the effect of motherhood on immigrant labor market integration in France from three regions of origin, as compared to native French women: immigrants from sub-Saharan Africa, the Maghreb (Algeria, Tunisia, and Morocco), and from European countries. (Each and every region of origin is considered separately in comparison to native French women). The results revealed substantial differences in the motherhood penalty between the different regions of origin and assert the existence of an especially pronounced motherhood penalty for mothers from the Maghreb. Given the gap in the research with regards to the cost of motherhood for immigrants in the labor market of the host country, this research sheds light on specific mechanisms influencing the integration patterns of immigrant women. Moreover, by choosing France, which is one of the main immigration destinations in Europe, and a country where the motherhood penalty for the native population is almost non-existent, this study provides a new perspective on the intersection of motherhood, immigration, and region of origin in the immigrants’ labor-market integration process.